Konsep Al-‘Ariyah, Al-Qardh dan Al-Hibah - Julfan Saputra; Sri Sudiarti; Asmaul Husna (Al-Sharf: Jurnal Ekonomi Islam, 2021)
The meaning of the contract in language is binding, binding. It is said that the bond (al-rabth) means to gather or collect the two ends of the rope and tie one of them to the other until the two are connected to become like a single rope. Al-ariyah (borrowing), al-qardh (debts), and al-Hibah (gifts) are forms of contracts that have always colored the development of Islamic economics in Indonesia in recent years. The purpose of this study is to analyze the concept of Al-'ariyah, Al-qardh and Al-Gift. This type of research is descriptive research with a library research approach. As for what is meant by library research, it is a research conducted by collecting books and other written sources that are needed and studying them. Sources of data used in this study is library data such as books (books), journals, and magazines. The results show that al-'ariyah (loans) is the provision of benefits of an item to others for free, whereas if it requires to be replaced with something or in return, it is no longer called al-'ariyah but is already al-qarh (debt). While al-Hibah (gift) is something that is given voluntarily without having to be replaced and returned. The three terms above are long-term investments that are useful for minimizing social risks and serve as a means of increasing awareness among human beings. Humans cannot live without the help and assistance of their brothers, there is no human being who has everything he needs in his life, al-'ariyah, al-qardh, and al-Hibah have become a part of human life in the world. Keywords: Al-'ariyah, Al-qardh, Al-Hibah